(untitled) (Journal of Environmental Microbiology and Toxicology, 2019)
Agricultural and industrial activities contribute most to the pollutants found globally; therefore, bioremediation of these pollutants is intensely sought. This research isolated a molybdenum-reducing bacterium from agricultural soil. The bacterium grown in low phosphate media (LPM) reduces molybadate to Mo-blue optimally at pH between 6.5 and 7.0, temperature between 35 and 40 Â°C, glucose at 5 g/L and glycine at 3 g/L were the best electron donor and nitrogen sources, respectively. The optimum molybdate concentration is between 80 and 100 mM, and phosphate concentration was between 5.0 and 7.5 mM. Phylogenetic analysis of 16S rRNA partial sequencing identified the bacterium as Enterobacter cloacae. The capacity of this bacterium to reduce toxic molybdenum to less toxic colloidal molybdenum blue is novel and form the basis for its use in future bioremediation of this pollutant.